(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
The important of ground water is increasing in the future as a source of fresh waters; in addition, many countries contain a number of water treatment plants to treat surface water. Using conventional treatment plant in the cities to treat ground water will decrease the cost of ground water treatment and may be help to depend on both surface and ground water supplies. This paper studied the ability of treating ground water by conventional water treatment. The quality of the ground water source is studied in the mention area during study period. The chemical quality of ground water is tested and there is within the standards of drinking water except iron. The conventional treatment was enhancing quality of treated water by increment of dissolved oxygen concentrations toward optimum value. Water treatment plant was effective for removal of iron from ground water of about 50%, in addition there is an effect of conventional treatment on sulfate removal (sulfate may be increase above standards in some ground water sources). The statistical analysis of data shows there is a correlation between quality parameters of raw and treated water and between iron and sulfate of treated water in the correlation matrix. In addition, confidence test was applied on the correlation coefficients using fisher’s transformation .The analysis shows, that there is a positive period (0.244, 0.941) of confidence of 95% of correlation factors of iron and sulfate.